Adaptive Governance and Climate Change - Brunner, Ronald D.; Lynch, Amanda H.; SpringerLink (Online service) (Boston, MA : American Meteorological Society : Imprint: American Meteorological Society, 2010)
As greenhouse gas emissions and temperatures at the poles continue to rise, so do damages from extreme weather events affecting countless lives. Meanwhile, ambitious international efforts to cut emissions (Kyoto, Copenhagen) have proved to be politically ineffective or infeasible. There is hope, however, in adaptive governance$1 (Ban approach that has succeeded in some local communities and can be undertaken by others around the globe. This book provides a political and historical analysis of climate change policy; shows how adaptive governance has worked on the ground in Barrow, Alaska, and other local communities; and makes the case for adaptive governance as a complementary approach in the climate change regime.s
Clarifying the Problem -- The Regime Evolves -- Barrow as Microcosm -- Opening the Regime -- Reframing the Context.
Keywords: Geography; Climatic changes; Environmental management; Earth Sciences; Climate Change; Atmospheric Sciences; Environmental Management